(untitled) (mathematica didactica, 2008)
Instruction- and subject-related convictions of mathematics teachers as components of professional knowledge can be content- and situation-specific on the one hand or rather general and not depending on particular situations on the other hand. As tasks play a central role for creating learning opportunities in mathematics instruction, convictions about tasks are considered to be contained in a rather situated domain of professional knowledge very relevant for instructional practice. The results of a study with 200 participating prospective teachers offer insight into convictions about modelling tasks, which might have an impact on the task-related classroom practice. Moreover, the results indicate correspondences with more general beliefs.